Integração cortical durante os processos de memória aversiva no lagarto Tropidurus Hispidus: uma avaliação do potencial de campo local e registro unitário de neurônios - Santos, Heitor Franco (2023)
INTRODUCTION: Electrophysiological studies contribute to understanding memory processes, such as encoding, consolidation, and recall, in different types of memory. Understanding how these processes occur in different groups of animals can contribute to elucidating evolutionary aspects, such as interregional communication in the brain and the physiological mechanisms involved. In this context, studies on memory in lizards are relevant, as their cortices have homologies with the mammalian hippocampus, and investigating their electrophysiological genesis can play a key role in better understanding the phenomenon at both the field activity and cellular levels. OBJECTIVES: This study aimed to evaluate the integration of the dorsomedial and lateral cortices in the lizard Tropidurus hispidus during aversive memory processes and initiate the characterization of the electrical activity of pyramidal neurons in the dorsomedial cortex. METHODS: T. hispidus lizards were used in two experiments. Experiment I (n = 30) focused on memory evaluation. The animals were divided into muscimol (MUS) and control (CTL) groups for each of the acquisition, consolidation, and evocation processes of aversive memory. The aversive stimulus exposure model included training and testing phases (habituation and exposure to a cat or a cage). Surgeries were performed to implant electrodes in the dorsomedial cortex (DMC) and lateral cortex (LC) and to insert guide cannulas in the lateral cortex for recording and pharmacological modulation, respectively. Memory processes were modulated through pharmacological intervention using muscimol (an inhibitory agonist) in the LC, with electrophysiological evaluation using electrodes. The drug infusion was directly into the LC, respecting each memory process. Behavior (freezing) and time and frequency domain analyses were performed. In Experiment II (n = 5), neuronal recordings (whole-cell patch-clamp) were conducted to characterize pyramidal neurons in the DMC of the reptilian hippocampus, focusing on intrinsic neuronal properties. RESULTS: The results showed that freezing response during the task was reduced in the MUS_AQ group compared to the other groups. The MUS_AQ group exhibited results that did not match its control or other groups. In functional evaluation, the MUS_AQ group did not dissociate exposure to the cat from the habituation period. In the frequency domain, the MUS_AQ group also showed impairments in power activity, coherence, and coupling, which are indicative of memory formation. When considering the overall context, it was observed that the main effect of the infusion was on the acquisition process and depended on communication between the LC and DMC. Characterization of ionic currents in pyramidal neurons of the DMC revealed the presence of short and long currents likely associated with potassium and an electrophysiological pattern that appears to be preserved across different reptiles and may be related to slow frequency patterns. CONCLUSION: Disturbances in the integration between the LC-DMC pathway impair memory encoding, highlighting the importance of integration for aversive memory acquisition. Neuronal recordings revealed repolarizing currents that may influence overall neuronal communication. Finally, the telencephalic cortex of T. hispidus shows functional homology with the mammalian hippocampus, and the findings of this study contribute to the knowledge of memory neurobiology and neuronal evolution characteristics in different groups of vertebrates.